Draft 7th Five Year Plan 1985-90 and Annual Plan 1985-86 Vol. IX Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
According to the data collected during the house listing Operations of 1981 census, Jammu and Kashmir State returned an aggregate number of 15.55 lakhs census houses. Of these only 7.02 lakhs houses were used wholly or partly for residential purposes. A comparison of the, data relating to -each of type two censuses Held during 1971 and 1981 reveals that there has been a growth rate of 12.13 per cent in the residential houses. The growth, rate has not obviously been commensurate with that of deferential population growth rise (1971-81 ) which is placed at 28.97 percent.
"Government of Jammu and Kashmir "
Planning and Development Department Jammu
Keywords: Housing; Police Housing; Jails; Urban Development; Non Functional Buildings; Functional Building; Stationery and minting Socp; Labour and Labour Welfare; I. T. I; Seventh Five Year Plan; Rental Housing Scheme; Land Acquisition and Development; Kashmir Division; Construction of Plats Under Self Financing Schemes; Seed Capital for Housing Board